The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/inf2.12148
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing light‐matter interaction in 2D materials by optical micro/nano architectures for high‐performance optoelectronic devices

Abstract: Two-dimensional materials are a promising solution for next-generation electronic and optoelectronic devices due to their unique properties. Owing to the atomic thickness of 2D materials, the light-matter interaction length in 2D materials is much shorter than that in bulk materials, which limits the performance of optoelectronic devices composed of 2D materials. To improve the light-matter interactions, optical micro/nano architectures have been introduced into 2D material optoelectronic devices. In this revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 169 publications
(370 reference statements)
0
62
0
Order By: Relevance
“…There have been extensive research efforts in integrating photonic structures with low‐temperature processed semiconductors, such as organic semiconductors, [ 1 ] colloidal quantum dots (QDs), [ 2 , 3 , 4 ] organohalide perovskites, [ 5 , 6 , 7 ] and 2D materials, [ 8 ] aiming at achieving high‐performance optoelectronic or optical devices with tunable functions and low fabrication cost. Among the semiconductors, colloidal QD is a particularly promising material family for interaction with photonic structures due to its high photoluminescence (PL) quantum yield, [ 9 ] widely tunable bandgap from ultraviolet (UV) to far‐wave infrared (IR), [ 10 ] great photostability, [ 3 ] and large surface‐to‐volume ratio that allows for various interface modification and functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…There have been extensive research efforts in integrating photonic structures with low‐temperature processed semiconductors, such as organic semiconductors, [ 1 ] colloidal quantum dots (QDs), [ 2 , 3 , 4 ] organohalide perovskites, [ 5 , 6 , 7 ] and 2D materials, [ 8 ] aiming at achieving high‐performance optoelectronic or optical devices with tunable functions and low fabrication cost. Among the semiconductors, colloidal QD is a particularly promising material family for interaction with photonic structures due to its high photoluminescence (PL) quantum yield, [ 9 ] widely tunable bandgap from ultraviolet (UV) to far‐wave infrared (IR), [ 10 ] great photostability, [ 3 ] and large surface‐to‐volume ratio that allows for various interface modification and functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…Many approaches, such as the construction of metal/2D structures, vdWs heterostructures, hybrid structures, and optical architectures, are useful for improving device performance (Figure 7a) [119,120]. In terms of optical architecture (cavities, waveguides, and plasmonics) integration, the plasmon structure enhances light absorption in 2D materials by enhancing local electromagnetic fields and subwavelength scattering, thereby enhancing the coupling of 2D materials with light.…”
Section: Photocurrent-enhanced Structure Of 2d Materialsmentioning
confidence: 99%
“…82 Due to the atomic-scale thickness of the 2D materials, the modulation depth of the 2D-based modulators is limited by the short lightmatter interaction length. 25 To this end, various structural designs have been proposed, such as employing structures with optical cavities, capacitor, and reflection architecture. For instance, a stereo graphene-microfiber structure was constructed, which enabled a sufficient light-graphene interaction length, thus a modulation depth of 7.5 dB was obtained.…”
Section: Key Parameters For Evaluating Thz Modulationmentioning
confidence: 99%
“…Exceptional physical properties (i.e., high mobility, mechanical flexibility, nonlinear optical response, and bandgap tunability) combined with the versatility of operation, may enable the 2D materials to modulate THz waves with superior performance and unleash the potentials of THz optoelectronic. 25,26 In this review, we discussed the progress of 2D-materials-based THz modulators with the frame shown in Figure 1. A brief overview of the fundamental properties of 2D materials, including graphene, TMDCs, and BP, is presented.…”
Section: Introductionmentioning
confidence: 99%